Making Thymus Visible: Understanding T-Cell Development from a New Perspective - Aghaallaei, Narges; Bajoghli, Baubak (Frontiers in Immunology, 2018)
T-cell development is coupled with a highly ordered migratory pattern. Lymphoid progenitors must follow a precise journey; starting from the hematopoietic tissue, they move towards the thymus and then migrate into and out of distinct thymic microenvironments, where they receive signals and cues required for their differentiation into naïve T-cells. Knowing where, when, and how these cells make directional “decisions” is key to understanding T-cell development. Such insights can be gained by directly observing developing T-cells within their environment under various conditions and following specific experimental manipulations. In the last decade, several model systems have been developed to address temporal and spatial aspects of T-cell development using imaging approaches. In this perspective article, we discuss the advantages and limitations of these systems and highlight a particularly powerful in vivo model that has been recently established. This model system enables the migratory behavior of all thymocytes to be studied simultaneously in a noninvasive and quantitative manner, making it possible to perform systems-level studies that reveal fundamental principles governing T-cell dynamics during development and in disease.